RESPIRATION AND PROTEIN SYNTHESIS IN ESCHERICHIA COLI MEMBRANE-ENVELOPE FRAGMENTS : I. Oxidative Activities with Soluble Substrates - Hendler, Richard W. (The Rockefeller University Press, 1969)
This paper describes experiments conducted with membranous and soluble fractions obtained from Escherichia coli that had been grown on succinate, malate, or enriched glucose media. Oxidase and dehydrogenase activities were studied with the following substrates: nicotinamide adenine dinucleotide, reduced form (NADH), nicotinamide adenine dinucleotide phosphate, reduced form (NADPH), succinate, malate, isocitrate, glutamate, pyruvate, and α-ketoglutarate. Respiration was virtually insensitive to poisons that are commonly used to inhibit mitochondrial systems, namely, rotenone, antimycin, and azide. Succinate dehydrogenase and NADH, NADPH, and succinate oxidases were primarily membrane-bound whereas malate, isocitrate, and NADH dehydrogenases were predominantly soluble. It was observed that E. coli malate dehydrogenase could be assayed with the dye 2,6-dichlorophenol indophenol, but that porcine malate dehydrogenase activity could not be assayed, even in the presence of E. coli extracts. The characteristics of E. coli NADH dehydrogenase were shown to be markedly different from those of a mammalian enzyme. The enzyme activities for oxidation of Krebs cycle intermediates (malate, succinate, isocitrate) did not appear to be under coordinate genetic control.